PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN LE MINERALE DI KECAMATAN MEDAN POLONIA DENGAN PROMOSI SEBAGAI VARIABEL MODERASI - Pertiwi, Suci (Jurnal Riset Akuntansi & Keuangan, 2023)
This research is to determine the effect of product quality, brand image, and price on the purchasing decisions of Le Minerale with promotion as a moderating variable (Case Study on Consumers in Medan Kota District). The type of research used in this research is quantitative research. The technique of determining the sample in this study used a nonprobability sampling technique with the Accidental sampling method from a google form link for 100 samples, namely Le Minerale consumers. The data analysis method used is Partial Least Square – Structure Equation Modeling with a two-stage approach test using the SmartPLS application version 3.2.9. The results of the significance test show that the exogenous variables, namely product quality, brand image, and price, have no effect on purchasing decisions. The result of the moderation test is that promotions are able to moderate the relationship between product quality and brand image with purchasing decisions, while promotions are unable to moderate prices with purchasing decisions of Le Minerale in Kota Medan.